A critical stakeholder perspective for examining sustainability of peer-to-peer rental platforms: An illustration in the French context - Loussaief, Leïla; Clauzel, Amélie (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2025)
Using a stakeholder approach, this research challenges the sustainability claim of the sharing economy practice of peer-to-peer rental. The discourses are compared using Natural Language Processing in relation to different French stakeholders (public institutions, press, platforms, consumers). Divergences emerge around the issue of sustainability and ownership. At the macro and meso levels, the discourse is centered on a neoliberal, economic approach to the phenomenon. Sustainability is scarcely mentioned, and greater emphasis is placed on economic benefits and gains for the individual. While ownership is also neglected at the macro-meso level, the discourse at the micro level shows a willingness to consume differently (depending on the product category and individual status), while still giving a central role to ownership.